2019
DOI: 10.21303/2504-5695.2019.001001
|View full text |Cite
|
Sign up to set email alerts
|

Research of Quality Indicators of Protein-Fat Mixture From Flax and Sesame Seeds for Nutrition of Athletes

Abstract: The aim of the research is to determine the microbiological stability of a protein-fat mixture of flax and sesame seeds that allows to correct its storage life. A protein-fat mixture has a high content of irreplaceable amino acids ВСАА and polyunsaturated fatty acids of w-3group, so it may be positioned as a component of nutrition for athletes. Flax and sesame seeds, cultivated in Ukraine, were used as research materials. The product was created, based on comminuted flax and sesame seeds in ratio 1:1. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the works [7,8], the composition of a protein-fat mixture for special purposes is proposed for the rational nutrition of athletes. The obtained research results found further development in the development of balanced amino acid composition of food systems based on oilseed meal and animal protein [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the works [7,8], the composition of a protein-fat mixture for special purposes is proposed for the rational nutrition of athletes. The obtained research results found further development in the development of balanced amino acid composition of food systems based on oilseed meal and animal protein [9].…”
Section: Introductionmentioning
confidence: 99%